Using marine isoscapes to infer movements of oceanic migrants: The case of Bulwer's petrel, Bulweria bulwerii, in the Atlantic Ocean. - Marta Cruz-Flores; Teresa Militão; Raül Ramos; Jacob González-Solís (PLoS ONE, 2018)
Studying the movements of oceanic migrants has been elusive until the advent of several tracking devices, such as the light-level geolocators. Stable isotope analysis (SIA) offers a complementary approach to infer areas used year-round, but its suitability in oceanic environments remains almost unexplored. To evaluate SIA as a tool for inferring movements of oceanic migrants, we sampled an oceanic seabird, the Bulwer's petrel, Bulweria bulwerii, in four breeding colonies spread along its Atlantic distribution. We first studied the species moulting pattern from 29 corpses collected in the colonies. Secondly, based on this moult knowledge, we selected three feathers from tracked birds to infer their breeding and non-breeding grounds using SIA: the 1st primary (P1), the 8th secondary (S8) and the 6th rectrix (R6) feathers. Birds migrated to two main non-breeding areas, the Central or the South Atlantic Ocean. P1 showed similar isotopic values among petrels from different breeding colonies, suggesting this feather is replaced early in the non-breeding period in a common area used by most birds, the Central Atlantic. S8 and R6 feathers correctly assigned 92% and 81%, respectively, of the birds to their non-breeding areas, suggesting they were replaced late in season, when birds were settled in their main non-breeding grounds. Our results showed that the isotopic baseline levels of the Central and South Atlantic are propagated through the food web until reaching top predators, suggesting these ratios can be used to infer the movement of long-distance migrants among oceanic water masses.